The Influence of Education Level, Income Level, Taxpayer Awareness, Social Environment, and Tax Sanctions on Taxpayer Compliance in Paying Land and Building Tax in 2021 : Case Study in Dolopo District, Madiun Regency - Susanto; Sri Hartono; Wijianto (Malaqbi Publisher, 2026)
This study aims to analyze the effect of Education Level, Income Level, Taxpayer Awareness, Social Environment, and Tax Sanctions on Land and Building Taxpayer Compliance in Dolopo District, Madiun Regency. This research is classified as quantitative research. The population in this study consists of all Land and Building Taxpayers who have Land and Building Tax objects in the Dolopo District, Madiun Regency. The technique of determining the sample is non-probability sampling, using purposive sampling. The number of samples in this study was 100 respondents, calculated using the Slovin formula. The method of data analysis in this study is multiple linear regression analysis, which was performed using SPSS version 25. The results of the study show that Education Level, Income Level, Taxpayer Awareness, Social Environment, and Tax Sanctions have a significant positive effect on Land and Building Taxpayer Compliance. Simultaneously, Education Level, Income Level, Taxpayer Awareness, Social Environment, and Tax Sanctions have a significant positive effect on Land and Building Taxpayer Compliance.